2014
DOI: 10.3109/02699052.2014.965207
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, vestibulo-ocular and cervicogenic post-concussion disorders: An evidence-based classification system with directions for treatment

Abstract: Future studies incorporating neuro-imaging and exercise science techniques are underway at the author's institutions to validate this novel pathophysiological approach to acute concussion and PCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
210
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 258 publications
(218 citation statements)
references
References 75 publications
7
210
0
1
Order By: Relevance
“…In accordance with our previous study, 13 we defined VOD as those patients with more than 1 subjective complaint of intermittent blurred or double vision; visual disturbance; difficulty concentrating, focusing, or reading; dizziness; or motion sensitivity, and the presence of more than 1 of the following objective physical examination findings: abnormal near-point convergence (NPC), abnormal extraocular movements or smooth pursuits, or abnormal or symptomatic assessment of horizontal saccades, vertical saccades, or vestibulo-ocular reflexes (VORs). 12 The presence of VOD was assessed at initial consultation for all patients with acute SRC and PCS.…”
supporting
confidence: 93%
“…In accordance with our previous study, 13 we defined VOD as those patients with more than 1 subjective complaint of intermittent blurred or double vision; visual disturbance; difficulty concentrating, focusing, or reading; dizziness; or motion sensitivity, and the presence of more than 1 of the following objective physical examination findings: abnormal near-point convergence (NPC), abnormal extraocular movements or smooth pursuits, or abnormal or symptomatic assessment of horizontal saccades, vertical saccades, or vestibulo-ocular reflexes (VORs). 12 The presence of VOD was assessed at initial consultation for all patients with acute SRC and PCS.…”
supporting
confidence: 93%
“…27,30 Although these studies have identified several important clinical predictors of PCS among pediatric patients, limited attention has been paid to features of the physical examination that are associated with specific concussion symptoms and which together may provide important insight into the pathophysiological mechanisms mediating persistent symptoms. 13 The present study meets an urgent unmet need by introducing a novel clinical definition that uses a combination of subjective and objective clinical findings that can potentially identify patients at an elevated risk of developing PCS. In this study, 29% of patients with acute SRC and 63% of those with PCS met the clinical criteria for VOD at initial clinical consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to accurately identify the pretreatment physiological mechanisms governing persistent concussion symptoms (i.e., physiological, vestibular, or cervicogenic) will have an important impact on evaluating the effect of therapeutic interventions in future studies, especially given potential differences in natural history and responses to physiotherapy observed among these unique populations. 13,28 Although the focused vestibulo-ocular examination used in the present study may help physicians identify those pediatric patients with acute SRC who are at risk for PCS and who may benefit from physiotherapy interventions, the widespread incorporation of these tests into standardized sideline or office assessment tools to be used by health care providers without clinical training in neurological, neuroophthalmological, and vestibular examination must be approached with caution. Clinicians using these assessment techniques should not only appreciate the neuroanatomy and physiology that govern each test but should also be aware of the myriad neurological conditions that can present with abnormalities of vestibular and oculomotor function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as a part of the education process, patients and parents should be apprised that persistent postconcussion symptoms warrant additional investigation to determine their underlying causes. [39][40][41] After returning to play, planned, routine follow-up assessments should be conducted to ensure the adolescent's quality of life is not being compromised. Clinicians need to acknowledge the potential for postconcussion emotional sequelae and work with the injured adolescent to identify potential causes, thereby easing the transition to full recovery.…”
Section: Discussionmentioning
confidence: 99%